Zooplankton Community Structure Based on Different Depths at the Kambang River Estuary, Pesisir Selatan Regency West Sumatra - Selvia, Seli; Siregar, Sofyan Husein; Nurrachmi, Irvina (Jurnal Perikanan dan Kelautan, 2023)
This research was conducted in March 2022 at the estuary of the Kambang River, Pesisir Selatan Regency, West Sumatra. This study aims to analyze the structure of the zooplankton community based on depth. The method used is a survey method by determining the sampling location by purposive sampling and zooplankton sampling points by stratified sampling. Sampling of zooplankton utilizing a water pump and filtered using plankton net no. 25, then brought to the laboratory to be identified and the community structure calculated. Sampling was accompanied by water quality pH, temperature, salinity, brightness, current velocity and DO measurements. Four zooplankton species were found in the Kambang River Estuary: Aetideus armatus, Macrosetella sp., Oithona sp., and Cyclops sp. The average value of zooplankton abundance during the day ranged from 1,938.61 - 2,492.50 ind/L, and in the afternoon 1,938.61 - 2,769.45 ind/L, the diversity index during the day was 1.28 - 1.55 and in the afternoon 1.28 - 1.36, the index of uniformity during the day was 0.72 - 0.98 and in the afternoon 0.86 - 0.98, while the index of dominance during the day was 0.40 - 0.53 and in the afternoon 0.40 - 0.52. The one-way ANOVA test results obtained an average value of 0.010 during the day and 0.029 in the afternoon, meaning there was a significant difference in zooplankton abundance between research depths